Description of the final instar larva of Anisocentropus diana Malicky & Chantaramongkol 1994 (Trichoptera: Calamoceratidae) in Thailand - Poepetch, Sakol; Prommi, Taeng-On; Laudee, Pongsak (Zootaxa, 2021)
The last instar larval stage of a Southeast Asian species Anisocentropus diana Malicky & Chantaramongkol 1994 (Trichoptera: Calamoceratidae) is described and illustrated based on Thai specimens. The larva of A. diana is different from known larvae of the other East Asian species A. kawamurai (Iwata) and A. magnificus (Ulmer) in its reddish-brown head without any patterns, the head’s large ventral apotome, and the abdominal gill arrangement.